Computação evolutiva aplicada ao problema da geração de grade horária: o caso do Curso de Análise e Desenvolvimento de Sistemas do IFTM - Freitas, Jairo Gervásio de (2012)
The development of timetable in educational institutions at the beginning of a semester is a complex and lengthy process for course coordinators or responsible, for it must meet various needs of those involved. The situation worsens when each teacher is available to teach classes only in some periods of the week. As the grid generation process is very specific to each institution, as each has its restrictions, it becomes difficult to create a solution that meets all institutions. To assist this process, performed manually in many institutions, this work aims, using the concept of genetic algorithms to create a system that generates a timetable in minutes that meets the specific of course of Analysis and Development Systems at the Federal Institute of Triangulo Mineiro, college Uberaba.